Preparation method and application of europium-doped zinc oxide graphene composite filler

By using europium ion Eu3+ doped zinc oxide nanorods and graphene composite fillers, early corrosion self-warning and long-term corrosion protection of ship anti-corrosion coatings were achieved, solving the problems of unclear signals and poor environmental stability in existing technologies and improving corrosion protection performance.

CN121293802APending Publication Date: 2026-01-09SHANGHAI CHINA SHIPBUILDING MATERIALS ENG CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511582909.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing ship anti-corrosion coatings lack early warning functions for corrosion, and the existing self-warning technology signals are not obvious and have poor environmental stability, making it difficult to be effective in harsh environments for a long time. Furthermore, it is difficult to achieve the same level of density, adhesion and long-term anti-corrosion performance as the base coating.

Method used

Europium ion (Eu3+) doped zinc oxide nanorods and graphene composite fillers are used to achieve early warning of corrosion through changes in fluorescence signals. Combined with the long-term anti-corrosion properties of zinc oxide, a conductive network is formed to prevent contact with corrosive media.

Benefits of technology

It enables intuitive and quantitative early warning of early corrosion, improves the performance of anti-corrosion coatings, and does not impair the protective life and mechanical properties of the coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293802A_ABST
    Figure CN121293802A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of europium-doped zinc oxide graphene composite filler. The preparation method comprises the following steps: (1) dissolving zinc nitrate and europium nitrate in deionized water; adding hexamethylenetetramine to obtain a mixed solution; transferring the mixed solution into a high-pressure reaction kettle, and reacting at 120-200 DEG C; after cooling, centrifuging, washing and carrying out vacuum drying to obtain Eu-ZnO NRs powder; (2) adding graphene oxide into ethylene glycol, and performing ultrasonic dispersion to form dispersion liquid; adding Eu-ZnO NRs powder, and carrying out ultrasonic mixing; adding hydrazine hydrate, and carrying out reflux reaction at 65-95 DEG C; and centrifuging, washing and drying to obtain the europium-doped zinc oxide graphene composite filler. The europium-doped zinc oxide graphene composite filler disclosed by the invention is used for ship anticorrosive paint, a conductive network can be constructed, the corrosion resistance is enhanced, and corrosive media such as seawater and oxygen are prevented from being in contact with a metal surface, so that the occurrence of corrosion is slowed down or prevented.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of ship metal anticorrosive coating, and particularly relates to a preparation method of europium-doped zinc oxide graphene composite filler and application thereof in ship anticorrosive coating, in particular to a preparation method of a composite filler based on rare earth europium ion (Eu 3+ ) doped zinc oxide nanorod and graphene and application thereof in ship anticorrosive coating, which realizes early corrosion self-warning through fluorescence signal change. BACKGROUND

[0002] Ships are long-term served in an extreme corrosion environment of high salt, high humidity, strong ultraviolet light and microbial attachment, which continuously threatens the integrity of the ship structure. In this environment, a high-performance anticorrosive coating is a key defense line to protect the safety of the ship and prolong the service life.

[0003] At present, widely used epoxy zinc-rich, epoxy cloud iron and other coatings mainly rely on the “passive protection” mechanism of physical shielding and cathodic protection. However, once the coating produces microcracks or local damage during service, and these defects are difficult to be detected in the early stage, the corrosion medium will quickly invade, causing irreversible corrosion of the base metal. Due to the lack of damage warning function, maintenance is often delayed, which not only greatly increases the maintenance cost, but also buries serious safety hazards, causing huge economic losses.

[0004] In order to realize early corrosion identification, researchers have developed pH-responsive color-changing coatings, microcapsule-type coatings and other self-warning technologies. However, these technologies still have significant limitations. The color change of the pH-responsive coating is difficult to observe in a dark environment, and the dye is prone to aging and fading in outdoor environment, resulting in signal failure; the microcapsule-type coating faces problems such as complex preparation process, poor uniformity of capsule distribution, insufficient mechanical reliability and the like, which makes it difficult to ensure long-term effectiveness. Overall, the existing self-warning technologies generally have common defects such as non-obvious signal, poor environmental stability and inability to quantitatively evaluate the damage degree. At the same time, the introduction of these functional layers often cannot be compatible with the compactness, adhesion and long-term corrosion resistance of the base coating, which restricts their practical application in harsh engineering environments.

[0005] Eu 3+ As a common rare earth luminescent element ion, europium ion Eu 3+Directly used in anticorrosive coatings, it is prone to fluorescence quenching, poor dispersion in polymer matrix and other problems, resulting in unstable signal and functional failure. On the other hand, zinc oxide (ZnO) nanomaterial is an important wide band gap semiconductor, which has certain physical shielding effect and potential for photo-induced cathodic protection. However, the single ZnO material has limited anticorrosion mechanism and cannot provide corrosion status feedback.

[0006] Patent document CN112374528A discloses a low-temperature preparation method for uniformly loading zinc oxide nanoparticles on the surface of graphene. By using 1-pyrene carboxylic acid to modify graphene, and combining zinc acetate and alkali solution for long-time reaction at 0-15°C, high-density and uniform distribution of zinc oxide on the surface of graphene is achieved. The composite material solves the problems of uneven distribution of nanoparticles and low loading density in traditional methods. However, this method has a long reaction period: it needs to be stirred at low temperature (0-15°C) for more than 7 days, which is low in production efficiency and not suitable for large-scale industrialized rapid preparation.

[0007] Patent document CN112844062A discloses a ceramic microfiltration membrane material for oil-water separation and water treatment. Rare earth elements (cerium, yttrium) are doped into zinc oxide, and then combined with graphene, and finally mixed with a ceramic substrate to press into a membrane. The membrane has photocatalytic degradation ability, which can effectively prevent organic pollutants from adsorbing on the membrane surface, and solves the problem of "secondary pollution" of ceramic membranes. However, this document does not belong to the field of ship anticorrosive coatings.

[0008] Patent document CN112844358A discloses a method for preparing three-dimensional structure graphene using amino graphene as raw material and polyurethane sponge as template, and then growing zinc oxide nanorods on the surface of the three-dimensional structure graphene by seed planting and hydrothermal reaction. This document effectively avoids the agglomeration problem of graphene and zinc oxide, and improves the photocatalytic performance of the composite material. However, the loading amount of zinc oxide is only about 120 mg per sample, which may not be efficient in high loading demand scenarios (anticorrosive coatings).

[0009] Patent document CN118341417A discloses a method for constructing a crown-shaped nano-zinc oxide structure on a substrate by using multiple processes such as atomic layer deposition, magnetron sputtering, hydrothermal reaction, plasma etching and electrodeposition, and further modifying rare earth oxides (such as lanthanum oxide, cerium oxide, etc.). This document solves the problems of narrow light absorption range and low quantum efficiency of traditional zinc oxide, but the process is extremely complex, involving more than five steps such as atomic layer deposition (ALD), magnetron sputtering, hydrothermal reaction, plasma etching and electrodeposition. The equipment is expensive and the process window is narrow, which can only be prepared in the laboratory and is difficult to scale up.

[0010] The prior art lacks a kind of Eu 3+The coating system combines the high-sensitivity fluorescent response characteristics of Eu-doped ZnO with the excellent long-term corrosion resistance of ZnO (or other materials), and can realize intuitive and quantitative early warning of early corrosion while not damaging the protective life and mechanical properties of the coating. SUMMARY

[0011] The application aims to provide a preparation method of Eu-doped ZnO graphene composite filler and its application in ship anticorrosive coating. 3+ The coating system combines the high-sensitivity fluorescent response characteristics of Eu-doped ZnO with the excellent long-term corrosion resistance of ZnO (or other materials), and can realize intuitive and quantitative early warning of early corrosion while not damaging the protective life and mechanical properties of the coating.

[0012] To achieve the above-mentioned purpose, the technical solution adopted by the application is: The application provides a preparation method of Eu-doped ZnO graphene composite filler, which comprises the following steps: (1) Dissolve zinc nitrate (Zn(NO3)2·6H2O) and europium nitrate (Eu(NO3)3·6H2O) in deionized water, wherein the molar ratio of Eu 3+ to Zn 2+ is 1:(30-50); add hexamethylenetetramine (HMTA) in an equal molar amount of zinc nitrate to obtain a mixed solution; transfer the mixed solution to a high-pressure reaction kettle, and react at 120-200°C for 2-8h; after cooling, centrifugally collect the product, wash, and vacuum dry at 50-80°C for 6-15h to obtain Eu-ZnO NRs powder (rare earth europium ion-doped zinc oxide nanorod); (2) Add graphene oxide (GO) to ethylene glycol, and ultrasonically disperse to form a dispersion liquid with a concentration of 0.5-6mg / mL; add the Eu-ZnO NRs powder, and ultrasonically mix; add hydrazine hydrate in an amount sufficient to reduce the graphene oxide, and reflux at 65-95°C for 8-18h; after centrifugation, washing, and drying, obtain Eu-doped ZnO graphene composite filler (Eu-ZnO NRs / rGO).

[0013] Preferably, in the Eu-ZnO NRs powder, the molar doping concentration of europium ions is 1%-5%, and more preferably, the molar doping concentration is 2%.

[0014] Preferably, in the step (2), the mass ratio of the graphene oxide (GO) to the Eu-ZnO NRs powder is 1:(5-10), and more preferably, the mass ratio is 1:10.

[0015] Preferably, in step (2), the dispersion is achieved by stirring at a speed of 1800-3000 rpm for 20-50 min using a high-speed shear machine.

[0016] The europium-doped zinc oxide graphene composite filler of the present invention is used in marine anti-corrosion coatings to improve the anti-corrosion performance of marine coatings.

[0017] More specifically, the present invention provides a europium-doped zinc oxide graphene marine anti-corrosion coating, comprising component A and component B in a mass ratio of (1-1.5):0.5. Component A is made from raw materials comprising the following mass fractions: epoxy resin 45%-50%, europium-doped zinc oxide graphene composite filler (Eu-ZnO NRs / rGO) 5%-10%, dispersant 1%-2%, solvent 30%-45%, leveling agent 0.05%-0.3%, and defoamer 0.05%-0.3%. Component B is a low-viscosity, solvent-free amino silicone resin. The epoxy resin is a bisphenol A type epoxy resin with an epoxy value of 0.41 to 0.47 mol / 100g and a viscosity of 10,000 to 20,000 mPa·s at 25°C, such as grades E-44 and E-51. The dispersant is a high molecular weight phosphate ester dispersant, such as BYK-190 manufactured by BYK Chemical Company; the leveling agent is a polyether siloxane, such as TEGO Flow 370 manufactured by TEGO Company; the defoamer is a polysiloxane-polyether copolymer, such as EFKA 2526 manufactured by Efka Company. The solvent is at least one of deionized water, propylene glycol methyl ether, propylene glycol methyl ether acetate, and ethanol. Preferably, component B is an amino polysiloxane resin with a viscosity of 100-500 mPa·s at 25°C and an amine value of 2-5 mmol / g, such as SILRES HP2020 manufactured by WACKER GmbH, Germany.

[0018] The present invention discloses a method for applying europium-doped zinc oxide graphene marine anti-corrosion coating, comprising the following steps: mixing the europium-doped zinc oxide graphene composite filler (Eu-ZnO NRs / rGO), dispersant, and solvent of a certain amount, and pre-dispersing to form a uniform and stable slurry; mixing the slurry with epoxy resin, residual solvent, leveling agent, and defoamer, and stirring until uniform to obtain component A; mixing component A with component B in proportion, maturing for 15-45 minutes, and applying it to a sandblasted metal substrate by brushing or spraying; after surface drying at room temperature, curing at 50-80℃ for 12-36 hours to form an anti-corrosion coating.

[0019] Compared with the prior art, the beneficial effects of the present invention are: This invention employs europium ions (Eu) 3+ The coating system, which organically combines the highly sensitive fluorescence response characteristics with the excellent long-lasting anti-corrosion properties of ZnO, forms a europium ion (Eu) coating system. 3+ The fluorescence intensity of zinc oxide nanorods (Eu-ZnO NRs) doped with zinc oxide (Eu-ZnO NRs) is affected by the OH groups generated during corrosion. - The ion-sensitive material enables early corrosion self-warning through changes in fluorescence signals. Zinc oxide nanorods are then loaded onto reduced graphene oxide (rGO), which serves as the growth framework for Eu-ZnO NRs, solving their dispersion problem. Applying the europium-doped zinc oxide graphene composite filler (Eu-ZnO NRs / rGO) of this invention to marine anti-corrosion coatings can construct a conductive network, enhancing anti-corrosion performance and preventing contact between corrosive media such as seawater and oxygen and the metal surface, thereby slowing down or preventing corrosion and improving its performance in marine anti-corrosion coatings. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope image of the europium-doped zinc oxide graphene composite filler (Eu-ZnO NRs / rGO) of the present invention. Detailed Implementation

[0021] Those skilled in the art should recognize that this embodiment is only used to illustrate the present invention and is not intended to limit the present invention. Any changes or modifications to the embodiment within the scope of the present invention are within the scope of the claims of the present invention.

[0022] Example 1 A method for preparing europium-doped zinc oxide graphene composite filler includes the following steps: (1) Dissolve 0.5949 g (0.002 mol) zinc nitrate (Zn(NO3)2·6H2O) and 0.0178 g (0.00005267 mol) europium nitrate (Eu(NO3)3·6H2O) in 40 ml of deionized water and stir magnetically for 30 min; add 0.2804 g (0.002 mol) hexamethylenetetramine (hexamethylenetetramine, HMTA) as an alkali source and structure directing agent to obtain a mixed solution; The mixed solution was transferred to a polytetrafluoroethylene-lined high-pressure reactor and reacted at 120°C for 6 hours. After natural cooling, the product was collected by centrifugation, washed three times alternately with deionized water and ethanol, and dried under vacuum at 60°C for 12 hours to obtain 0.2 g of Eu-ZnO NRs powder (rare earth europium ion-doped zinc oxide nanorods). Approximately 0.2 g of dried Eu-ZnO NRs powder was obtained (yield calculated based on ZnO as 80%). 3+ With Zn 2+The molar ratio is 1:38, and the molar doping concentration of europium ions is 2%. (2) Take 20 ml of commercially available GO dispersion with a concentration of 1 mg / ml (containing 20 mg of GO), add 20 ml of ethylene glycol, and sonicate for 1 h to ensure that the GO is evenly dispersed to form a dispersion with a concentration of 0.5 mg / mL; add 0.200 g of dried Eu-ZnO NRs powder, and continue sonicating for 2 h to fully mix the nanorods with the GO sheets; add 20 μL of hydrazine hydrate and stir magnetically for 15 min; then reflux in an oil bath at 95 °C for 12 h to reduce GO to rGO, while making Eu-ZnO NRs firmly attached to the rGO sheets to form a three-dimensional heterostructure; after centrifugation, washing and drying, europium-doped zinc oxide graphene composite filler (Eu-ZnO NRs / rGO three-dimensional composite) powder with a three-dimensional composite structure is obtained.

[0023] A europium-doped zinc oxide graphene marine anti-corrosion coating, the formulation of its component A is listed in Table 1, and its application method includes the following steps: S1, Eu-ZnO NRs / rGO composite filler, dispersant (BYK-190) and 50% of the formulated amount of solvent (propylene glycol methyl ether) are mixed and dispersed by shearing with a high-speed shear machine at 2000 rpm for 30 min to form a uniform and stable slurry; the slurry is mixed with epoxy resin (E-44), residual solvent, leveling agent (TEGO Flow 370) and defoamer (EFKA 2526) and mechanically stirred at 500 rpm for 60 min until uniform to obtain component A; S2. Mix component A and component B (amino polysiloxane resin, SILRES HP2020) at a mass ratio of 1:0.5 and allow to mature for 15 minutes. Apply the mixture to a sandblasted titanium alloy substrate by brushing or spraying. After surface drying at room temperature, cure at 60°C for 24 hours to form an anti-corrosion coating.

[0024] Table 1. Formulation of Component A of Europium-doped Zinc Oxide Graphene Marine Anticorrosion Coating, Unit: wt% Example 2 The preparation method of europium-doped zinc oxide graphene composite filler is basically the same as that in Example 1, except that in step (1): 0.5949 g of zinc nitrate (Zn(NO3)2·6H2O) and 0.0061 g of europium nitrate (Eu(NO3)3·6H2O) are dissolved in 40 ml of deionized water and magnetically stirred for 30 min. The molar doping concentration of europium ions is 1%.

[0025] The preparation method for the anti-corrosion coating used on ships is the same as in Example 1.

[0026] Example 3 The preparation method of europium-doped zinc oxide graphene composite filler is basically the same as that in Example 1, except that in step (1): 0.594 g of zinc nitrate (Zn(NO3)2·6H2O) and 0.0305 g of europium nitrate (Eu(NO3)3·6H2O) are dissolved in 40 ml of deionized water and magnetically stirred for 30 min; Eu 3+ With Zn 2+ The molar ratio is 5:100, and the molar doping concentration of europium ions is 5%.

[0027] The preparation method for the anti-corrosion coating used on ships is the same as in Example 1.

[0028] Example 4 The preparation method of europium-doped zinc oxide graphene composite filler is basically the same as that in Example 1. The difference is that in step (1): 0.100 g of dry Eu-ZnO NRs powder is added and ultrasonication is continued for 2 hours to fully mix the nanorods with the GO sheets and ensure that the mass ratio of GO to Eu-ZnO NRs is 1:5.

[0029] A europium-doped zinc oxide graphene marine anti-corrosion coating, the formulation of its component A is listed in Table 1, and its application method includes the following steps: S1, Eu-ZnO NRs / rGO composite filler, dispersant (BYK-190) and 40% of the formulated amount of solvent (propylene glycol methyl ether) are mixed and dispersed by shearing with a high-speed shear machine at 2000 rpm for 50 min to form a uniform and stable slurry; the slurry is mixed with epoxy resin (E-51), residual solvent, leveling agent (TEGO Flow 370) and defoamer (EFKA 2526) and mechanically stirred at 600 rpm for 50 min until uniform to obtain component A; S2. Mix component A and component B (amino polysiloxane resin, SILRES HP2020) at a mass ratio of 1:0.4 and allow to mature for 25 minutes. Apply the mixture to a sandblasted titanium alloy substrate by brushing or spraying. After surface drying at room temperature, cure at 55°C for 30 hours to form an anti-corrosion coating.

[0030] Example 5 The preparation method of europium-doped zinc oxide graphene composite filler is basically the same as that in Example 1. The difference is that in step (1): 0.1500 g of dry Eu-ZnO NRs powder is added and ultrasonication is continued for 2 hours to fully mix the nanorods with the GO sheets and ensure that the mass ratio of GO to Eu-ZnO NRs is 1:7.5.

[0031] A europium-doped zinc oxide graphene marine anti-corrosion coating, the formulation of its component A is listed in Table 1, and its application method includes the following steps: S1, Eu-ZnO NRs / rGO composite filler, dispersant (BYK-190) and 45% of the formulated amount of solvent (propylene glycol methyl ether) are mixed and dispersed by shearing with a high-speed shear machine at 2000 rpm for 40 min to form a uniform and stable slurry; the slurry is mixed with epoxy resin (E-51), residual solvent, leveling agent (TEGO Flow 370) and defoamer (EFKA 2526) and mechanically stirred at 800 rpm for 30 min until uniform to obtain component A; S2. Mix component A and component B (amino polysiloxane resin, SILRES HP2020) at a mass ratio of 1:0.6 and mature for 40 minutes. Apply the mixture to a sandblasted titanium alloy substrate by brushing or spraying. After surface drying at room temperature, cure at 70°C for 20 hours to form an anti-corrosion coating.

[0032] Comparative Example 1 Comparative Example 1 is a comparative example of Example 1 and is basically the same as Example 1, except that europium nitrate is not added in step (1) and the doping concentration of europium ions is 0%.

[0033] Comparative Example 2 Comparative Example 2 is a comparative example of Example 1 and is basically the same as Example 1, except that graphene GO is not added in step (4).

[0034] Test Experiment Example The anti-corrosion coatings of Examples 1-5 and Comparative Examples 1-2 were tested. The test methods and results are shown in Table 2.

[0035] Table 2 Performance test results of coatings in Examples 1-5 and Comparative Examples 1-2 Note: In a 3.5 wt% NaCl solution, the artificially scratched areas of the coating can be excited by a UV lamp (365 nm) within 1 hour to produce bright red fluorescence, while the intact areas show no fluorescence.

[0036] The results in Table 2 show that the marine anti-corrosion coatings formulated using the europium-doped zinc oxide graphene composite filler (Eu-ZnONRs / rGO three-dimensional composite) prepared in Examples 1-5 exhibit high europium ion content. 3+The high-sensitivity fluorescence response characteristics of the sample were excellent, while no fluorescence signal was observed in Comparative Example 1 without europium ions. Comparative Example 2 lacked the barrier effect and conductive network of rGO, resulting in a significantly weakened cathodic protection effect. The Eu-ZnO NRs severely aggregated in the resin, leading to a fluorescence quenching effect. The fluorescence signal was very weak or uneven, and the coating uniformity was poor. The corrosion resistance was significantly lower than in Examples 1-5, demonstrating the indispensability of the synergistic effect between rGO and Eu-ZnO NRs.

Claims

1. A method for preparing europium-doped zinc oxide graphene composite filler, characterized in that, Includes the following steps: (1) Dissolve zinc nitrate and europium nitrate in deionized water, wherein Eu 3+ With Zn 2+ The molar ratio was 1:(30-50); hexamethylenetetramine, in equimolar amounts with zinc nitrate, was added to obtain a mixed solution; the mixed solution was transferred to a high-pressure reactor and reacted at 120-200℃ for 2-8 hours; after cooling, the product was collected by centrifugation, washed, and vacuum dried at 50-80℃ for 6-15 hours to obtain Eu-ZnONRs powder. (2) Add graphene oxide to ethylene glycol and ultrasonically disperse it to form a dispersion with a concentration of 0.5-6 mg / mL; add the Eu-ZnO NRs powder and ultrasonically mix it thoroughly; add hydrazine hydrate to reduce the amount of graphene oxide and reflux at 65-95°C for 8-18 h. After centrifugation, washing, and drying, europium-doped zinc oxide graphene composite filler was obtained.

2. The preparation method of europium-doped zinc oxide graphene composite filler according to claim 1, characterized in that, The molar doping concentration of europium ions in the Eu-ZnO NRs powder is 1% to 5%.

3. The preparation method of europium-doped zinc oxide graphene composite filler according to claim 1, characterized in that, In step (2), the mass ratio of graphene oxide (GO) to the Eu-ZnO NRs powder is 1:(5-10).

4. The preparation method of europium-doped zinc oxide graphene composite filler according to claim 1, characterized in that, In step (2), the dispersion is achieved by stirring at a speed of 1800-3000 rpm for 20-50 min using a high-speed shear machine.

5. The europium-doped zinc oxide graphene composite filler obtained by any one of the preparation methods according to claims 1 to 4 is used in marine anti-corrosion coatings.

6. A europium-doped zinc oxide graphene marine anti-corrosion coating, characterized in that, The product is composed of component A and component B in a mass ratio of (1-1.5):0.

5. Component A is made from raw materials comprising the following mass fractions: 45%-50% epoxy resin, 5%-10% europium-doped zinc oxide graphene composite filler, 1%-2% dispersant, 30%-45% solvent, 0.05%-0.3% leveling agent, and 0.05%-0.3% defoamer. Component B is a low-viscosity, solvent-free amino silicone resin.

7. The europium-doped zinc oxide graphene marine anti-corrosion coating according to claim 6, characterized in that, The epoxy resin is a bisphenol A type epoxy resin with an epoxy value of 0.41 to 0.47 mol / 100g and a viscosity of 10,000 to 20,000 mPa·s at 25°C.

8. The europium-doped zinc oxide graphene marine anti-corrosion coating according to claim 6, characterized in that, The dispersant is a high molecular weight phosphate ester dispersant, the leveling agent is a polyether siloxane, and the defoamer is a polysiloxane-polyether copolymer.

9. The europium-doped zinc oxide graphene marine anti-corrosion coating according to claim 6, characterized in that, The solvent is at least one of deionized water, propylene glycol methyl ether, propylene glycol methyl ether acetate, and ethanol.

10. The europium-doped zinc oxide graphene marine anti-corrosion coating according to claim 6, characterized in that, Component B is an amino polysiloxane resin with a viscosity of 100-500 mPa·s at 25°C and an amine value of 2-5 mmol / g.

11. The application method of the europium-doped zinc oxide graphene marine anti-corrosion coating according to any one of claims 6 to 10, characterized in that, Includes the following steps: The europium-doped zinc oxide graphene composite filler, dispersant, and solvent are mixed and pre-dispersed to form a uniform and stable slurry. The slurry is then mixed with epoxy resin, residual solvent, leveling agent, and defoamer and stirred until homogeneous to obtain component A. Component A is mixed with component B in a certain proportion and allowed to mature for 15–45 minutes. The mixture is then applied to a sandblasted metal substrate by brushing or spraying. After surface drying at room temperature, the coating is cured at 50–80°C for 12–36 hours to form an anti-corrosion coating.

Citation Information

Patent Citations

  • Graphene surface loaded zinc oxide nanoparticle composite material as well as preparation method and application thereof

    CN112374528A

  • Preparation method of graphene-rare earth doped zinc oxide nano ceramic microfiltration membrane composite material

    CN112844062A

  • Preparation method of graphene zinc oxide nano composite material

    CN112844358A

  • Preparation method and application of rare earth modified nano zinc oxide composite layer material

    CN118341417A